Experience in Hepatic Arterial Infusion (HAI) with 5FU Due to Liver Metastases in Patients (Pts) with Colorectal Cancer (CC) - Wcisło, Gabriel; Korniluk, Jan; Brzozowski, Krzysztof; Osiecki, Mirosław; Nurzyński, Paweł; Twarkowski, Paweł; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Background: Hepatic Artery Infusion (HAI) with anticancer agents is a palliative treatment for liver metastases. This study has been initiated to assess the efficacy and safety of bolus injections of 5FU through arterial catheters fixed to the hepatic artery. Materials and Methods: Between July, 1996 to June, 1999-38 patients (pts) (male 25, female 13) aged 19-75 (mean 58,4) with pathologically proved colorectal cancer (cc) liver metastases have been treated with HAI. All pts had no extrahepatic measurable malignant disease. Karnofsky status >60%. 5FU was given over 10-15 minutes, in doses 800-1 000 mg/m 2 in 100 ml of 5% dextrose + 5000 j. heparin + 20 mg dexamethasone. The procedure was repeted every 4 weeks. 189 courses of HAI were completed in all pts (4,97 courses a pt). Efficacy of the treatment was done every 3-4 months. The distribution of time to progression and survival were estimated using the method of Kaplan-Meier. Control group consisted of 40 pts (male 26, female 14), aged 36-75 (mean 59,8) with multiple cc liver matastases who have not been treated with HAI. Results: All pts received 138 courses of HAI. Toxicities were observed: thrombocytopenia G2 in two pts after 6 courses (4,5%), leucopenia G4 in one pt after 5 courses (3,6%), fever G4 in one pt after 2 courses (1,5%), stomatitis G3 and G4 in two pts after 10 courses (7,2%). In addition, 6 pts (15,8%) were complicated by bleeding out from the catheter insertion site. Tumor reaction on the treatment was observed: 3 pts (8%) - CR, 1 (2,6%) - PR, 18 pts (47%) - SD. The median survival of pts without HAI was 10 + 6,29 mo. The median time to progression was 6,38 + 3,80 mo. One and two year survival rates were 45% and 20 % respectively. Of 38 pts 17 (45%) are alive and 21 (55%) died of disease. Overall survival this group of pts was 15,31±9,46 mo and controls 10,27±6,12 mo and was statistically significant (p 5 cm and number of loci >3 were independent factors of poor prognosis. Conclusion: HAI due to liver metastases in pts with cc seems to be a palliative procedure giving the possibility for longer live.